Aggregation-disaggregation-switched sensing strategy for copper(II) ion and histidine in aqueous solution and living cell imaging. (December 2019) - Zhang, Qian; Zhang, Peng; Li, Shasha; Fu, Caixia; Ding, Caifeng
Abstract: Histidine level has been reported to reflect human health, and its precise detection demand was challenging and highly desired. By virtue of facile construction of coordinated complexes, a novel sensing assay for histidine detection based on copper(II) complex of perylene-3, 4, 9, 10-tetracarboxylic acid tetrapotassium salt ensembles (PTAK-Cu 2+ ) was developed, which was generated in situ in aqueous solution. The coordination ligand PTAK showed superior affinity to Cu 2+ over other metal ions, and the highly ordered assemblies exhibited quenched fluorescence caused by the aggregation procedure. Cu 2+ could be captured by competitive coordination with histidine, which triggered the disaggregation of PTAK-Cu 2+ assemblies, giving rise to a significant increase of PTAK monomer fluorescence and the relevant colorimetric changes were visible by the naked eye. The detection strategy for histidine offered a detection of limit as low as 24.9 nM with good linearity, and was also workable for cellular imaging. Graphical abstract: Image 1 Highlights: A sensing assay for histidine based on perylene ensembles PTAK-Cu 2+ was developed. Cu 2+ was captured by histidine leading to the disaggregation of PTAK-Cu 2+ assemblies. The detection strategy for histidine offered a LOD of 24.9 nM in aqueous solution. The probe can be applied for intracellular imaging with the help of TAT.